PEMBUATAN E-COMMERCE UNTUK TOKO PERALATAN JARINGAN KOMPUTER SEBAGAI PENINGKAT NILAI BISNIS MENGGUNAKAN CMS - Fian Yulio Santoso; Eko Sediyono; Irwan Sembiring (Program Studi Teknik Informatika, 2022)
At this time, there is an opportunity for computer network equipment stores because internet traffic is increasing and requires a quality network. However, these opportunities also increase competition between computer network equipment stores. To deal with this problem, you can use online marketing, but not all marketplaces are right for online marketing in this case study because some marketplaces already have many sellers and the prices of goods are very competitive therefore, other ways are needed to do online marketing but can minimize the level of competition. This research was carried out using a survey and implementation method to deal with this problem. This research shows that online marketing is needed by creating a marketplace using a CMS. After an in-depth analysis of the best CMS for online marketing, opencart was chosen because it best suited the business case. Furthermore, the evaluation results showed more than 100 visits in the evaluation period which lasted for 1 week. This shows that the application of online marketing using the OpenCart CMS can increase visits by potential buyers compared to before doing online marketing.